2016
DOI: 10.3138/jvme.0315-034r1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Laparoscopic Skills in Veterinarians Using a Canine Laparoscopic Simulator

Abstract: The aim of the present study was to assess the content and construct validity of the Canine Laparoscopic Simulator (CLS). Forty-two veterinarians were assigned to experienced (n=12), control (n=15), and training (n=15) groups, which were assessed while performing four laparoscopic tasks on the CLS. The initial and final assessments of all tasks were performed blindly by two experienced surgeons using the Global Operative Assessment of Laparoscopic Skills (GOALS) and a task-specific checklist. At the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…24 The results of the survey strongly support the introduction of structured simulator training in veterinary residency programs, as has recently been developed for laparoscopic training. [36][37][38][39][40][41] Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost. In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…24 The results of the survey strongly support the introduction of structured simulator training in veterinary residency programs, as has recently been developed for laparoscopic training. [36][37][38][39][40][41] Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost. In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties.…”
Section: Discussionmentioning
confidence: 55%
“…The overall lack of availability and use of simulators reported in this study suggests that there is limited appreciation of the types and merits of simulator training along with concerns regarding financial and time investment . The results of the survey strongly support the introduction of structured simulator training in veterinary residency programs, as has recently been developed for laparoscopic training . Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost.…”
Section: Discussionmentioning
confidence: 60%
“…During simulator laparoscopic training, attendants were asked to perform five tasks on a previously validated canine physical simulator. 25 They began by practicing basic skills with hand-eye and hand-hand coordination tasks and cutting on inorganic tissue and continued with advanced maneuvers while practicing dissection and intracorporeal suturing on ex vivo porcine stomachs. Simulator thoracoscopic training included lymph node dissection and lung biopsies on ex vivo porcine cardiopulmonary systems.…”
Section: Methodsmentioning
confidence: 99%
“…7 This is surprising, since simulation training is the first step to learn laparoscopic surgical skills, its usefulness having been reported both in human and veterinary medicine. 13,25,29 Certainly, Kilkenny et al showed that simulation provides an effective platform for veterinary students (and likely novice laparoscopic surgeons), to learn laparoscopic intracorporeal suturing. 29 In addition, Chen et al compared two training curricula, the first centered on basic surgery skill training and the second based on procedures (including both physical and virtual reality simulation), and found that both improved veterinary students laparoscopic skills.…”
Section: Laparoscopy and Thoracoscopy Training And Implementationmentioning
confidence: 99%
“…The traditional surgical apprenticeship is still relevant but less practical for many smaller clinical units, as it is time-and resource-consuming and limits the passage of knowledge and skills to one trainee at a time. Simulator training under proctorship is more applicable on a wider scale and facilitates the passage of knowledge and skills passed from one expert to multiple persons through workshops and regular skills training on reliable tissue models 13,42,43 . It has been suggested that, because of its rarity, TTTS treatment should be accumulated in high-volume fetal centers to improve its outcomes.…”
mentioning
confidence: 99%